Our commitment : The World Bank's Africa Region HIV/AIDS Agenda for Action 2007-2011 - World Bank (Washington, DC, 2012)
The World Bank is committed to support sub-Sahara Africa in responding to the HIV/AIDS epidemic. This Agenda for Action is a road map for Bank management and staff over the next five years to fulfill that commitment. It focuses on mainstreaming HIV/AIDS activities into broader national development agendas as a critical aspect of economic growth and human capacity development. In preparing the Agenda for Action, consultations have been carried out over several months with a broad constituency, including countries, donors, communities and nonprofit organizations.